ANALISIS BENTUK RAGAM HIAS, FUNGSI DAN MAKNA ULOS BATAK DALAM ADAT MASYARAKAT MANDAILING SUMATRA UTARA - Nuriah Harahap; Ernis Ernis (Universitas Negeri Padang, 2020)
This research aims to, know the form of ornaments in Ulos, the function of Ulos in the traditional life of Batak Mandailing people and the meaning of Ulos, anvariety of ornamental that exist in Batak Mandailing people. This type of researchnis qualitative by descriptive methods. Data collection techniques are done bybobservation, interviews and documentation. analyzed data are collection, reduction, presentation and taking conclusions. The results showed that there are 2 Ulos Mandailing which has the same ornamental form but different in size and function. Ulos are formed from the interwoven yarn feed and lumbar so as toproduce various kinds of decorative shapes, all forms of ornamental plants that exist in Ulos have the meaning and experience the shape of the form.Keyword: analysis, function and meaning of Ulos Batak